Dynamic heterogeneous scheduling method based on Stackelberg game model in container cloud - Wei ZENG; Hongchao HU; Lingshu LI; Shumin HUO (网络与信息安全学报)
Container technology promotes the rapid development of cloud computing with its flexible and efficient features, but it also introduces security threats such as co-resident attacks, escape attacks, and common mode attacks.In response to these security threats, a dynamic heterogeneous scheduling method based on Stackelberg game in the container cloud was proposed.First, a heterogeneous mirrored resource pool is constructed to suppress the spread of attacks based on common-mode vulnerabilities on the cloud.Then, the offensive and defense interaction process is modeled as a Stackelberg game model.Finally, the offensive and defensive model is analyzed, and the system scheduling problem is modeled as a mixed integer non-linear programming problem to solve the system's optimal scheduling strategy.Experiments show that the proposed method can improve the defense effect of the cloud platform and reduce the system defense overhead.